Edukasi Penyebaran Covid-19 dan Pembagian Masker Dalam Upaya Mencegah Penyebaran Covid-19 - Markani, Markani; Sulehu, Marwah; Ratnawati, Ratnawati; Syamsu, Suryadi; Awaliah, Neneng (Universitas Gorontalo, 2023)
The spread of Covid-19 has become a concern for both the public and the government. With the increasing rate of spread, the government is more responsive and issued various policies. One of the government's policies to suppress the spread of the corona virus is the use of masks outside the home. This requires people to always wear masks and pay attention to their respective health. In accordance with the analysis in the field, there are still many residents who do not care about the use of masks, so it is necessary to provide education about the dangers of transmitting COVID-19 if they do not use masks outside the home. The method used in this activity is the lecture method to residents and the direct distribution of masks to residents and the distribution of masks to the nearest hospital from the campus location. As a result, residents who previously did not use masks immediately use them right away so they can know the importance of using masks in suppressing the spread of the COVID-19 virus.